Goodness That Frees from “Game of Values”: On Deconstruction of Axiological Thinking - Małecka, Magdalena (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
The aim of this article is to show that metaphysical level is the core and condition of possibility of axiology. The paper focuses on methodological differentiation concerning two levels: metaphysical and axiological one. The first one is connected with Goodness, which is the essence of values and an atmosphere that precedes every evaluation, while the second one means discourse about values. When metaphysical level with its Goodness is forgotten, axiology changes itself into “game of values”, that arbitrarily builds hierarchy and tries to measure everything. This “game of values” discounts the level of Goodness and functions as a closed area – a system of rules, where there are only  pseudo-values (goods), but there is no reference to Goodness. Without taking into consideration the metaphysical (i.e. ethical in Levinasian terminology) level and personal thinking axiology shows itself as a totalitarian construct, which only seems to be interested in Goodness and in fact it is more focused on constructing values. The difference between metaphysics and axiology is described via phenomenological analysis of Enigma of Goodness (the order of metaphysics) and phenomenon of good (the order of axiology).